The Archaeology of the Courts’ Domestic Violence Discourse: Discourse as a Knowledge-Sustaining System - Ohana, Natalie (feminists@law, 2020)
In the last several years, the harm of coercive control has been increasingly acknowledged as a domestic violence harm by the England and Wales legal system. In this process of growing acknowledgement of the harm it inflicts in intimate relationships, coercive control is being inserted into existing discourses around domestic violence. The article examines the impact of a discourse on the understanding of a harm: how can the understanding of coercive control be impacted by the structure of the discourse into which it is inserted? The courts’ civil domestic violence discourse in England and Wales and its potential impact on the understanding of coercive control is examined as a case study. Using critical theory which links knowledge to social power as an analytical lens, the discourse is seen as not only founded upon a harm that is entirely detached from women’s experiences but also as a knowledge-sustaining system, operating on an everyday basis to protect and to further strengthen that alienated knowledge. Through its knowledge-sustaining operation, the discourse prevents a meaningful change in the legal understanding of domestic violence, a change that is required for coercive control to be integrated into the discourse in a way that will reflect its essence and severity.